Expansion volume of amaranth grain in local populations and improved varieties - Ramírez-Pérez, Ana Rosa; Ortiz-Torres, Enrique; Argumedo-Macías, Adrián; De la O-Olán, Micaela; Jacinto-Hernández, Carmen; Ocampo-Fletes, Ignacio (Revista Mexicana de Ciencias Agrícolas, 2022)
In Mexico, the common form of commercialization and consumption of amaranth is as popped grain. However, there are few studies on the diversity in the expansion volume of grain in amaranth species and populations. The objective was to assess the diversity in expansion volume of grain in 36 local populations and improved varieties of amaranth. Grains from a field evaluation in four locations carried out in 2015 and 2016 were used. A 6 x 6 lattice experimental design with two repetitions was used. In 2018, the expansion volume of popped grain was evaluated. Thirty-six varieties of amaranth were used, of which 30 were populations of the municipality of Tochimilco, Cohuecan and Huaquechula, Puebla, Mexico and the Amaranteca, Benito, Nutrisol, Revancha, Laura and Gabriela varieties. The samples were conditioned to 12% moisture and popped in fluidized bed machine by hot air at a temperature of 230-235 °C. After the popping, the weight and volume of the grain popped and not popped were recorded. An analysis of variance and mean test were performed. The results show that there were statistical differences (p≤ 0.01) between varieties and localities for all the characters evaluated. In expansion volume, the range of variation was from 6.2 to 10.6 ml g-1. In the quality by popped grain size, 24 collections were outstanding in large and medium popped size.
Keywords: hectoliter weight; kernel weight; Amaranthus hipochondriacus; Amaranthus cruentus